PROBLEM-PROBLEM MINORITAS TRANSGENDER DALAM KEHIDUPAN SOSIAL BERAGAMA - RR Kurnia Widiastuti (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Transgender individual is one of minority in our society. Transgender people has problem with their body and feeling. Their physical appearances do not match with their psychological aspect. Therefore they are assumed by majority society as“abnormal” people. As a result they tend to be discriminated and marginalized from the society. As a human being, transgender individual has the same right as other individuals of the society. Therefore as religious people, transgender individuals have freedom to express their belief. However, they find several problems in their living existences in social religious context.Kata Kunci: transgender, minoritas, hak beragama, abnormal, dan diskriminasi